Languages, disciplines, and prefixes: Implications and scope of multi, inter, and trans thought - Céspedes, Lucía (2024)
This presentation sought to reflect upon the prefixes historically used to name those entities which cannot be bounded to a single, fixed, discreet category. Contributions from Linguistics were taken as a starting point to then extrapolate its concepts to the analysis of scientific practice in general. Thus, first, different conceptions of linguistic relations were compared and contrasted: from mono to bi, multi, inter, and finally, translingualism, with special attention to power issues, border demarcation, and speaker characterization in each of these paradigms. Second, a correspondence between analogous categories which describe and study contacts among scientific disciplines (multi, inter and transdiscipline) was tried out. Finally, the reach and limitations of applying this linguistic metaphor to the analysis of hybridization and exchanges within the scientific field were assessed, as well as its potential to induce changes in knowledge classification and production practices.